A critique of monetary policy : theory and British experience - Dow, J. C. R.; Saville, I. D. (Oxford : Clarendon Press : New York : Oxford University Press, 1988)
This book is an essay in theory, and a study of monetary policy in practice. It is an examination of how monetary policy has worked, or failed to work, in the United Kingdom in the 1970s and 1980s. This book is theoretical more than historical, and bears on the general question of the effects to be attributed to monetary policy at any time.
Includes index.
Bibliography: p. [249]-254.
usc 26/07/2017
Loans
Keywords: Monetary policy; Interest rates; Interest rates--Government policy; Chicago school of economics; Great Britain